Analisis Kesiapan Perbankan Dalam Implementasi Green Financing : Tinjauan Komparatif Bank Syariah Dan Bank Konvensional Di Indonesia - Ningtyas, Devy Ayu; Nurafini, Fira (Tasharruf : Journal of Islamic Economics and Business, 2024)
Environmental pollution, air pollution and other problems related to the environment. Pollution is an economic problem. Therefore, policy makers require economic development to truly implement a green vision in the new era. The proactive role of banking is necessary to support the creation of environmentally friendly finance (green finance) as a lender that will stimulate industry to do this in implementing environmental management in line with maqasid sharia. This research aims to analyze the application of green financing and financial performance on capital returns in sharia and conventional banking 2019 - 2023. This research uses a purposive sam pling method with secondary data from sharia banks and conventional banks. The analysis technique used is Multiple Regression. This research was conducted to test the influence of variables including CAR, NPL, BOPO, and LDR which influence ROA in conventional banking. Meanwhile, Islamic banking tested the influence of variables including CAR, NPF, BOPO, and FDR which influenced ROA. The results of this research show that the influence of the CAR and LDR variables of Conventional Banks is positive and significant on ROA. Meanwhile, the NPL and BOPO variables of conventional banks have a negative and significant effect. Meanwhile, The influence of the variables CAR, NPF, BOPO and FDR of Islamic banks has no effect on ROA.